2009
DOI: 10.1080/09593330802685813
|View full text |Cite
|
Sign up to set email alerts
|

Measuring gas velocity in a duct as a specific function of a pressure‐balance‐type probe in an isokinetic dust sampler

Abstract: A probe of the pressure-balance type has been developed and used as part of an automatic isokinetic dust sampler. The aerodynamic characteristic of the probe was studied in order to determine the gas velocity when using this probe at its location in the duct. Such an anemometric function of the probe, together with an automatic control and logging of sampling parameters, maintains the isokinetic conditions during the sampling of dust-carrying gas and permits the online and in situ continuous measurement of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…w(∆p), by the central unit calculation module. This method and the aerodynamic characteristic itself are the results of previous research of the authors of this article, which they conducted for coaxial fl ows in relation to the axis of the conduit and the axis of the probe (Szulikowski and Kateusz 2009). Their other zero dust probe research (Kateusz et al 2004) has indicated for all the aspiration nozzles a lack of infl uence of gas turbulence on the aerodynamic characteristic w(∆p) -in the situation, when both the fl ow of gas and the setting of the aspiration nozzle are coaxial (i.e.…”
Section: Object and Range Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…w(∆p), by the central unit calculation module. This method and the aerodynamic characteristic itself are the results of previous research of the authors of this article, which they conducted for coaxial fl ows in relation to the axis of the conduit and the axis of the probe (Szulikowski and Kateusz 2009). Their other zero dust probe research (Kateusz et al 2004) has indicated for all the aspiration nozzles a lack of infl uence of gas turbulence on the aerodynamic characteristic w(∆p) -in the situation, when both the fl ow of gas and the setting of the aspiration nozzle are coaxial (i.e.…”
Section: Object and Range Of Researchmentioning
confidence: 99%
“…The authors have already investigated the above--mentioned fl ue gas velocity sensors (Kateusz 2000, Kateusz et al 2001, Kateusz et al 2004, Szulikowski and Kateusz 2009). One of the aspects of these studies was the impact of gas fl ow turbulence on the metrological properties of the sensors.…”
Section: Object and Range Of Researchmentioning
confidence: 99%
“…A method has been developed to take account of the characteristic profile decay in the vicinity of a wall and in corners during the measurement of mean velocity [14][15][16]6]. There are descriptions of point velocity measurements carried out by means of a zeropressure dust probe with an anemometric function [17], as well as the estimation of error of axial velocity measured with the use of pressure-type probes for actual local gas flow deviations in a conduit [18]. The quantitative assessment of some other types of distinctive errors in point velocity measurements might be adopted from the standard [19] concerned with the independent, accurate measurement of volumetric gas flow rates in uniform flows.…”
Section: Introductionmentioning
confidence: 99%